The Role of Adversity Quotient in Academic and Social Adjustment: A Study on Non-Local Students in Makassar - Asyah, Fahranil Fathirah; Nurhikmah, Nurhikmah; Thalib, Tarmizi (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
Non-local students often face significant challenges adjusting to their new academic and social environments. In college adjustment, it is necessary to have effort or fighting power (adversity quotient) to adapt to the place where they study. This quantitative study aims to examine the effect of the adversity quotient on college adjustment among non-local students in Makassar. The research participants consisted of 386 non-local students from outside South Sulawesi Province, currently in their first and second years of study in Makassar. The data collection instrument uses the College Self-Adjustment scale and the Adversity Quotient scale with a Likert scale model, both of which are modified scales. The data analysis technique used simple linear regression analysis with the help of SPSS software version 26. The results of this study prove that adversity quotient can have a significant influence on college adjustment (P=0.000; P<0.05). Subsequently, the percentage of adversity quotient contribution is 35.9% to college adjustment, while 64.1% is influenced by other variables that are not studied. Students who strive to adapt to the college environment will have good academic and non-academic performance and will survive in the following years. Conversely, students who make less effort to adapt to the college realm will have an impact on learning achievement results and feelings of dissatisfaction with their college experience.